Analysis of the Reproduction Traits and Milk Yield in Cows from Apuseni Mountains Farms - Ioan HAN; Otilia BOBIŞ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2019)
Milk production in cows is influenced by a series of factors with direct or indirect action upon its body. Farms from three counties in Apuseni Mountains (Alba, Bihor and Hunedoara) were monitorized for milk production and other reproductive attributes. Age of first calving, service period, calving interval and natality were the parameters monitorized in the study to determine the reproduction trains in the area of Apuseni Mountains. Analyzing the obtained data regarding the average production of milk, lactation duration in the studied counties, it is found that: on total lactation, the largest production was obtained in Bihor county with 4815.26 kg (332.6 days), followed by Hunedoara county with 4796.40 kg (325.6 days) and Alba county with 4528.05 kg ( 321.4 days). The obtained results, which reflect the current level of milk production in Apuseni Mountain area, show that the studied cows have a real productive potential, the average of the lactation yields as well as its duration, being at the upper limit of the breed, according also to specialized literature data. Breeding activity was found to be good but can be improved. Due to the great importance of reproduction, the economic and productive performance of dairy farms requires careful attention to its planning and management.